Going Deep: The Trade and Welfare Effects of TTIP Revised - Gabriel Felbermayr; Rahel Aichele; Inga Heiland (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2016)
Since July 2013, the EU and the United States have been negotiating a preferential tradeagreement, the Transatlantic Trade and Investment Partnership (TTIP). We use a multicountry, multi-industry Ricardian trade model with national and international inputoutput linkages to quantify its potential economic consequences. We structurally estimate the model's unobserved parameters and the effect of existing preferential tradeagreements on trade cost. With those estimates in hand, we simulate the trade, valueadded, and welfare effects of the TTIP, assuming that the agreement would eliminate alltransatlantic tariffs and reduce non-tariff barriers as other deep PTAs have done in thepast. We find a long-run increase of real income of .4% for the EU, by .5% for the UnitedStates, and by -.02% for the rest of the world relative to the status quo. However, thereis substantial heterogeneity across the 140 geographical entities that we investigate.Gross value of EU-US trade is predicted to increase by 50%, but the content of EU andUS value added would decrease, signalling a deepening of the transatlantic productionnetwork. Moreover, we quantify trade diversion effects on third countries and find thatthose are less severe for value added trade than for gross trade. This highlights theimportance of global value chains in understanding the effects of the TTIP on outsidersand the global economy.
Keywords: F13; F14; F17; 330; Structural gravity; preferential trade agreements; TTIP